Endoscopic ultrasound‐guided antegrade procedures for managing bile duct stones in patients with surgically altered anatomy: Comparison with double‐balloon enteroscopy‐assisted endoscopic retrograde cholangiography (with video). Issue 7 (9th February 2021) - Takasaki, Yusuke; Ishii, Shigeto; Shibuya, Tomoyoshi; Fujisawa, Toshio; Ushio, Mako; Takahashi, Sho; Ito, Koichi; Yamagata, Wataru; Suzuki, Akinori; Okahara, Koki; Okawa, Yoshihiro; Ochiai, Kazushige; et al.
Abstract : Background and Study Aim: Management of bile duct stones (BDSs) in patients with surgically altered anatomies (SAAs) remains challenging. An endoscopic ultrasound‐guided antegrade (EUS‐AG) procedure and double‐balloon enteroscopy‐assisted endoscopic retrograde cholangiography (DB‐ERC) have been used to remove BDSs from patients with SAAs. However, few comparative data have been reported. Therefore, we compared the efficacy and safety of the techniques. Methods: This was a single‐center retrospective study. Patients with SAA who underwent the EUS‐AG procedure or DB‐ERC to remove intra‐ or extra‐BDSs between November 2010 and March 2020 were included. The primary outcome was the technical success rate, defined as stent insertion or stone removal during the initial session. The secondary outcomes were the procedure time, incidence of adverse events (AEs), and complete stone removal rate. Results: Of the 54 patients enrolled, 23 underwent the EUS‐AG procedure and 31 DB‐ERC. The technical success rates of EUS‐AG and DB‐ERC were 87.0% and 64.5%, respectively ( P  = 0.11). The procedure time was significantly shorter in the EUS‐AG group than in the DB‐ERC group (51.9 ± 15.4 vs 72.6 ± 32.2 min; P  = 0.01), and the early AE rates were 26.1% and 12.9%, respectively ( P  = 0.71). The complete stone removal rates in patients who underwent previous stone removal were 94.1% in the EUS‐AG group and 85.7% in the DB‐ERC group ( P  = 0.61). Conclusion: The EUS‐AG afforded technical success and complete stone removal rates comparable with those of DB‐ERC, but the former procedure was shorter. The AE rate was acceptable.